1981
DOI: 10.1038/bjc.1981.21
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme and its association with outcome in lung cancer

Abstract: Summary.-Serum angiotensin-converting enzyme (SACE) in 141 patients with newly detected primary lung cancer was 22-1 + 6-1 nmol/ml/min (mean + s.d.); lower than in healthy controls (24.4 + 6-2 nmol/ml/min, P <0.02). No correlation was found between SACE and sex, age, site of cancer, histological type, or lung function.After subdivision of the patients according to increasing SACE levels: < 16.0 (mean SACE of lung cancer -s.d.), 16-0-22-0, 22-1-28-2, and >28-2 nmol/ml/min (mean SACE of lung cancer + s.d.) there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…This finding was corroborated by others, demonstrating low serum ACE levels in patients with lung tumors as compared to patients with other pulmonary diseases or carcinomas [40, 41]. The lowest serum ACE levels correlated with poor prognosis and higher relapse rate [39, 42, 43] as well as metastatic disease, suggesting that quantification of serum ACE may be a prognostic indicator for lung cancer [44]. Further, ACE activity increased in patients with bronchial carcinoma following chemotherapy or radiotherapy [41, 43, 45] as well as in patients in clinical remission [44].…”
Section: Angiotensin Peptide Synthesizing Enzymes and Lung Cancersupporting
confidence: 72%
See 1 more Smart Citation
“…This finding was corroborated by others, demonstrating low serum ACE levels in patients with lung tumors as compared to patients with other pulmonary diseases or carcinomas [40, 41]. The lowest serum ACE levels correlated with poor prognosis and higher relapse rate [39, 42, 43] as well as metastatic disease, suggesting that quantification of serum ACE may be a prognostic indicator for lung cancer [44]. Further, ACE activity increased in patients with bronchial carcinoma following chemotherapy or radiotherapy [41, 43, 45] as well as in patients in clinical remission [44].…”
Section: Angiotensin Peptide Synthesizing Enzymes and Lung Cancersupporting
confidence: 72%
“…Romer found that the serum ACE levels were significantly lower in 141 patients newly diagnosed with primary lung cancer as compared to healthy controls [39]. This finding was corroborated by others, demonstrating low serum ACE levels in patients with lung tumors as compared to patients with other pulmonary diseases or carcinomas [40, 41].…”
Section: Angiotensin Peptide Synthesizing Enzymes and Lung Cancermentioning
confidence: 70%
“…In the following decades, it has been suggested that elevated serum ACE could be implicated with a worse prognosis for lung cancer and that this enzyme could be used as a prognostic indicator in this disease [9]. In other studies, the treatment with combined Ang II showed good clinical response in the patients with advanced gastrointestinal cancer and also with breast cancer [10] [11]. Between 1985 and 1990 several works showed that RAS components were correlated with other cancers (prostate, gastric, bladder, bronchial, breast, lung and neuroblastoma) [12] [13].…”
Section: Renin Angiotensin System and Cancermentioning
confidence: 99%
“…Although individually low values were evenly distributed among the patients, it is known that some diseases (not included in this study) are associated with low enzyme activity, e.g. lung cancer [16] and some haematological and lymphatic malignancies [17]. A rather low SACE has also been reported in regional enteritis [22]; whereas a recent survey from our laboratory showed no difference from the reference series in yersinosis (SACE 27.7 i~ 6.5 kU/1, n = 7) or rheumatoid arthritis (SACE 22.2 f 4.6 kU/1, n = 21), these diseases being represented in this study.…”
Section: Patients Without Sarcoidosismentioning
confidence: 98%